Global Salafism Study of Roel Meijer's Views - Syukri, Syukri (International Journal of Islamic Khazanah, 2023)
This study aims to understand Roel Meijer's thoughts regarding Salafism, focusing on terms, doctrines, and their relation to politics and violence. Before 9/11, Salafism had not received significant attention from scholars. However, after this incident, Salafism and Wahhabism became important topics because they were related to political movements and violence in the name of religion. The method used in this study is Library Research with the Factual Historical Model, which examines the substance of the text that contains the thoughts and ideas of the figures as religious works as contained in the thoughts and works of the figures. Based on Roel Meijer's study, global Salafism originates from the inspiration of Wahhabism, founded by Muhammad bin 'Abd Wahab. Wahhabism has a doctrine of returning to the Koran and al-Hadith, purging monotheism from various polytheism, accepting ijtihad, and rejecting taqlid. The term "Salafi" refers to two groups: Salafi da'wah groups that are oriented towards improving individual, family, and community structures through da'wah and education, and Salafi groups that have the same goal but are politically inclined and tend to use violence, which is referred to as Salafi jihadis. This research contributes to a deeper understanding of Salafism, its doctrines, and its relation to politics and violence.